Penerapan Model Pembelajaran Teams Games Tournament (TGT) terhadap Kemampuan Pemahaman Konsep Matematis Siswa Di SMA Negeri 3 Aceh Barat Daya - Ulfa, Yulanda; Salasiyah, Cut Intan (Mathieu : Journal of Mathematics Education and Learning, 2026)
The purpose of this study was to determine the difference in students’ conceptual understanding abilities between those taught using the Teams Games Tournament (TGT) learning model and those taught using the direct learning model at SMA Negeri 3 Abdya. The TGT learning model consists of four stages: class presentation, group study, tournament, and group reward. The hypothesis of this study was that students taught using the TGT learning model would have better conceptual understanding abilities than students taught using the direct learning model. This study employed a quantitative approach with a Quasi-Experimental Design in the form of a pre-test and post-test control group design. The population of this study consisted of all tenth-grade students of SMA Negeri 3 Abdya. The samples were class X IPS 1 as the experimental class and class X IPS 2 as the control class. Data were collected through a conceptual understanding ability test. The sampling technique used was cluster sampling. The results showed that the TGT learning model was more effective in improving students’ mathematical conceptual understanding abilities than the direct learning model.and reseach results; written in 1 paragraph, single space among rows, using past tense sentences.